2020
DOI: 10.1097/prs.0000000000007509
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma: Evolving Role in Plastic Surgery

Abstract: Background: The use of platelet-rich plasma has emerged as one of the most desired nonsurgical treatments for facial rejuvenation and hair restoration. It has grown to encompass a wide variety of applications within the field of plastic surgery, including its use in combination with microneedling, laser, and fat-grafting procedures. Methods: In this article, the authors aim to (1) describe the preparation process of platelet-rich plasma; (2) discuss the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 98 publications
0
33
0
Order By: Relevance
“…In response to tissue and vascular damage, a platelet plug is formed, with the subsequent release from its alpha granules of more than 30 biologically active proteins, including: transforming growth factor β, platelet-derived factor, growth factor, vascular endothelial growth factor, fibroblast growth factor, and epithelial cell growth factor. These factors not only aid in clotting but also drive angiogenesis and promote tissue repair and regeneration [10]. Multiple authors have shown that topical application or intradermal injection of PRP and its growth factors produce favorable cutaneous changes: clinical (restores its vitality, increases its thickness, recovers its elastic consistency, improves blood circulation, increases its smoothness, decreases its wrinkles and improves their appearance) [2,10,11] histopathological (increases the number of fibroblasts, collagen fibers and blood vessel basement membranes) [2,10,12] immunohistochemical (improves collagen expression type I, III and IV) [13][14][15] and the genetic material (through the polymerase chain reaction expression of three target genes, such as: collagen IA, matrix metalloproteinase gene 1 and protein rich in proline of keratinocytes) [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to tissue and vascular damage, a platelet plug is formed, with the subsequent release from its alpha granules of more than 30 biologically active proteins, including: transforming growth factor β, platelet-derived factor, growth factor, vascular endothelial growth factor, fibroblast growth factor, and epithelial cell growth factor. These factors not only aid in clotting but also drive angiogenesis and promote tissue repair and regeneration [10]. Multiple authors have shown that topical application or intradermal injection of PRP and its growth factors produce favorable cutaneous changes: clinical (restores its vitality, increases its thickness, recovers its elastic consistency, improves blood circulation, increases its smoothness, decreases its wrinkles and improves their appearance) [2,10,11] histopathological (increases the number of fibroblasts, collagen fibers and blood vessel basement membranes) [2,10,12] immunohistochemical (improves collagen expression type I, III and IV) [13][14][15] and the genetic material (through the polymerase chain reaction expression of three target genes, such as: collagen IA, matrix metalloproteinase gene 1 and protein rich in proline of keratinocytes) [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…These factors not only aid in clotting but also drive angiogenesis and promote tissue repair and regeneration [10]. Multiple authors have shown that topical application or intradermal injection of PRP and its growth factors produce favorable cutaneous changes: clinical (restores its vitality, increases its thickness, recovers its elastic consistency, improves blood circulation, increases its smoothness, decreases its wrinkles and improves their appearance) [2,10,11] histopathological (increases the number of fibroblasts, collagen fibers and blood vessel basement membranes) [2,10,12] immunohistochemical (improves collagen expression type I, III and IV) [13][14][15] and the genetic material (through the polymerase chain reaction expression of three target genes, such as: collagen IA, matrix metalloproteinase gene 1 and protein rich in proline of keratinocytes) [13,14]. PRP has been used as an adjunct to multiple skin rejuvenation treatments (lipotransference, laser, peeling, lifting).…”
Section: Discussionmentioning
confidence: 99%
“…The considerable variations in PRP extraction, activation, and frequency of application can lead to significant discrepancies between study results and diminish comparability. Furthermore, the vast majority of the authors did not dis- The issue of high variation in PRP preparation protocols has been addressed on several occasions [3][4][5]. One of the contributing factors is the broad range of suggested classification systems.…”
Section: Limitationsmentioning
confidence: 99%
“…Adverse events reported in the reviewed literature are pain, edema, and ecchymosis at the microinjection site [1,2].…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Platelet Rich Plasma (PRP) is an autologous serum that contains high concentrations of platelets and growth factors. These growth factors are responsible for the mitogenesis and differentiation of monocytes, fibroblasts, stem cells, keratinocytes and endothelial cells, as well as inducing cell proliferation, angiogenesis and chemotaxis, in addition to containing serotonin, dopamine, histamine, adenosine and calcium, which increase the permeability of the membrane [1,2]. These qualities have made PRP a versatile therapy in dermatology; however, few studies objectively evaluate its efficacy, which motivated the conduct of the present investigation.…”
Section: Introductionmentioning
confidence: 99%